INFLUENCE OF NUCLEAR FACTOR κB INHIBITOR ON FUNCTIONAL STATUS OF SPERM IN WHITE RATS UNDER COMBINED EFFECT PRODUCED BY SODIUM NITRATE AND X-RAY IRRADIATION ON THE BODY - Shatalin, B.O.; Kostenko, V.O. (World of Medicine and Biology, 2016)
This experiment involved 28 white rats was designed to study the effect of nuclear factor κB (NF-κB) inhibitor – JSH-23 (4-methyl-N- (3-phenylpropyl) benzene-1,2-diamine) – on quantitative and qualitative indicators of sperm under the conditions combining chronic intoxication with sodium nitrate (200 mg / kg for 30 days) and exposure to X-rays (in a dose of 0.08 Gy three times a week on alternate days, for a total of 0.25 Gy). It has been shown the administration of JSH-23 (1 mg/kg, twice a week) in experimental conditions significantly reduces the percentage of non-viable cells and their pathological forms (with caput abnormalities). At the same time the motility of spermatozoa becomes impaired that is reflected in the cell increase with the rapid forward movement (normokinesis, category A), as well as sperm cells with oscillating disordered movement (dyskinesis, category C), reducing the cell with a slow forward movement (hypokinesis, category B) and fixed sperm (akinesis, category D).
Keywords: nuclear factor kappa B; nitrate intoxication; X-ray irradiation; spermiogram; kinesiogram